FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU BERGOTONG ROYONG MASYARAKAT DI KELURAHAN BAMBU KUNING TAHUN 2021 - Anastasya Shinta Yuliana; Marido Bisra; Ani Riza Wati (LPPM Universitas Awal Bros, 2021)
There are several things that are factors that influence mutual cooperation behavior such as the absence of a driving team and lack of support from related parties. Improving the behavior of mutual cooperation in the community of the yellow bamboo village is important because with the existence of mutual cooperation activities, it creates a clean environment. A clean environment certainly makes life healthy for humans because the environment plays an important role in the development of human life. Therefore we need care and attention to the environment around us in order to balance life in living daily life. The method used is lectures and posters, and activities are carried out at the Posyandu, Bambu Kuning Village on Saturday 27 March 2021 at 08.00 am until finished. The counseling materials provided include the objectives of mutual cooperation, the benefits of mutual cooperation and the presentation of data on the 10 biggest diseases in the yellow bamboo village. At the end of the counseling, the community understood the importance of mutual cooperation behavior and solutions were also found in order to improve mutual cooperation behavior such as the result of a mutual agreement between the RW heads, RT heads and the surrounding community, namely by making a mutual cooperation schedule for each RT in turn and determining the gotong royong post, which was set. at posyandu. And the driving team is the RW and RT heads in the yellow bamboo village.